Maintenance of Light-Standards-A Case-Study - Dekker, R.; van der Meer, J. R.; R. Ph. Plasmeijer; Wildeman, R. E.; de Bruin, J. J. (The Journal of the Operational Research Society, 1998)
This paper discusses several strategies for the maintenance of light-standards, where each light-standard consists of n independent and identical lamps screwed on a lamp assembly. The lamps are subject to stochastic failures, and must be correctly replaced if the number of failed lamps reaches a prespecified number m, a norm that is set by the local management to guarantee a minimum luminance. As lamps have an increasing hazard rate and there is a fixed cost of hoisting the assembly, we propose various variants of the m-failure group replacement rule which have in particular an age-criterion to indicate which of the non-failed lamps must be preventively replaced at the time that the assembly is lowered for a corrective lamp replacement. We show how the optimal threshold age can be determined. It appears that this modification reduces the long run average maintenance cost of the Europe Combined Terminals by approximately 8.3%.